Shi'i clerical networks and the transnational contest over sacred authority: dynamics in London's Shi'i Triangle. Issue 4 (1st November 2019) - Corboz, Elvire
Abstract : This article explores the transnational contest over sacred authority in contemporary Shi'i Islam as it plays out between contemporary maraji' (sources of emulation) and the Iranian Supreme Leader, and in practice between their respective networks. It engages with existing assessments of the marja'iyya as an institution in crisis and argues instead that the marja'iyya has structural capacities that help maintain its potential in the face of the power exerted by the Supreme Leader. This in turns shapes the nature and outcome of the contest, including the need for the latter to accommodate with competing religious authorities. In the first part, the article offers a conceptualisation of the marja'iyya 's potential on the basis of three of its intrinsic features: its polycephalic nature and the broad temporal and geographical scope of a marja' 's authority. The second part offers a case study of the transnational contest over sacred authority in a specific locale. It maps the various (institutionalised) networks associated with Middle Eastern authorities, the Supreme Leader included, in London. Networks are however not hard-bound entities, as illustrated by the cross-networks navigation of their members. Furthermore, networks operate not only in competition but also in collaboration with each other. The contemporary contest over Shi'i authority is thus not a zero-sum game.